2023
DOI: 10.1021/acsomega.3c01058
|View full text |Cite
|
Sign up to set email alerts
|

Methionine-Containing Peptides: Avoiding Secondary Reactions in the Final Global Deprotection

Abstract: The solid-phase synthesis of Met-containing peptides using a fluorenylmethoxycarbonyl (Fmoc)/tert-butyl (tBu) protection scheme is inevitably accompanied by two stubborn side reactions, namely, oxidation and S-alkylation (tert-butylation), which result in the formation of Met(O) and sulfonium salt impurities of the target peptide, respectively. These two reactions are acid-catalyzed, and they occur during the final trifluoroacetic (TFA)-based acidolytic cleavage step. Herein, we developed two new cleavage solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…On the other hand, solutions of Met in DMF, NFM, and DMSO gave minimal Met oxidation (entries 5–7), and the fact that these solvents were opened for >2 months suggested that they were not as prone to R-OOH formation on storage as NBP and NMP. Finally, as Met oxidation during TFA cleavage is a relatively facile process which has to be suppressed by suitable scavengers, ,, we assessed Met oxidation in TFA (entry 8), and as anticipated, an appreciable amount of Met(O) was formed. Nevertheless, the extent of the oxidation was far less than for the R-OOH-contaminated NBP and NMP (entries 1 and 4), suggesting that oxidation during SPPS, rather than during cleavage, might be a bigger concern when pyrrolidinone solvents such as NMP or NBP are used in peptide synthesis.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…On the other hand, solutions of Met in DMF, NFM, and DMSO gave minimal Met oxidation (entries 5–7), and the fact that these solvents were opened for >2 months suggested that they were not as prone to R-OOH formation on storage as NBP and NMP. Finally, as Met oxidation during TFA cleavage is a relatively facile process which has to be suppressed by suitable scavengers, ,, we assessed Met oxidation in TFA (entry 8), and as anticipated, an appreciable amount of Met(O) was formed. Nevertheless, the extent of the oxidation was far less than for the R-OOH-contaminated NBP and NMP (entries 1 and 4), suggesting that oxidation during SPPS, rather than during cleavage, might be a bigger concern when pyrrolidinone solvents such as NMP or NBP are used in peptide synthesis.…”
Section: Resultsmentioning
confidence: 94%
“…While we previously reported that oxidation-sensitive amino acids such as Cys and Trp undergo N -oxyl radical-caused degradation in DMF, ,, we did not observe appreciable Met oxidation under these conditions. In fact, while preventing Met oxidation during peptide resin cleavages has been thoroughly investigated, Met oxidation during peptide synthesis has been less studied . In fact, in some cases Met oxidation during synthesis can be so cumbersome, that a less oxidation-prone AA instead of Met is used, and we thus set out to investigate the impact of hydroperoxides in NBP, as well as other SPPS solvents, on the oxidation of Met and other oxidizable AAs and peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it was interesting to note that replacement of the V-4 residue of peptide 1 with proline (17) had a significantly detrimental effect on PPI disruption activity, while the proline analogue of 4 (18) 52 was also inactive. Peptides 1 -3, all of which were tetrazole-containing analogues of MEEVD, which displayed the most promising Hop TPR2A -HSP90 CTD PPI disruption, were then assessed for their ability to disrupt the fulllength Hop-HSP90 PPI, again using an ELISA based solid phase assay (Figure 4A).…”
Section: Structure-activity Relationship Of Ppi Disruptionmentioning
confidence: 99%
“…The desired product was accompanied by numerous byproducts, including substantial amounts of free-thiol intermediates. We then came across a recent report by Yang et al, who established that TIS can reduce Cys disulfide bonds formed on the solid phase during the cleavage and deprotection step in TFA. , We therefore substituted hydrosilane with thioanisole. Interestingly, doing so resulted in the clean formation of the target oxo SEA peptide 6a , albeit with slow kinetics (Table , entry 2).…”
mentioning
confidence: 99%